Impact of achieving a complete response to initial therapy of multiple myeloma and predictors of subsequent outcome. Issue 3 (3rd January 2022) - Kaddoura, Marcella; Binder, Moritz; Dingli, David; Buadi, Francis K.; Lacy, Martha Q.; Gertz, Morie A.; Dispenzieri, Angela; Kapoor, Prashant; Hwa, Lisa; Fonder, Amie; Hobbs, Miriam; Hayman, Suzanne; et al.
Abstract: Achievement of a complete response (CR) in multiple myeloma (MM) correlates with improvement in survival outcomes; however, its impact on prognostic variables at baseline outside of clinical trial settings is not well described. We sought to determine the impact of achieving a CR within 2 years from diagnosis, its effect on the prognostic value of fluorescence in situ hybridization (FISH) and International Staging System (ISS) risk, and examined additional predictors of outcome among those achieving a CR in a routine clinical setting. We evaluated 1869 newly diagnosed MM patients who had ≥ 2 monoclonal protein immunofixation studies in the serum and urine available within 24 months from diagnosis, categorizing those with ≥ 2 negative serum and urine immunofixations as achieving CR. With a landmark at 24 months, median progression‐free survival (PFS) for CR versus non‐CR patients was 29.8 versus 20.9 months ( p  ≤ .0002); median overall survival (OS) was 104 versus 70 months ( p  < .0001). The impact of achieving a CR was retained after adjusting for FISH, ISS, sex, transplant status, and involved heavy chain. Baseline FISH and ISS stage were not associated with PFS or OS among patients achieving a CR. The following variables were found as predictors of inferior OS within the CR cohort: age > 75 years, male gender, hypoalbuminemia, and non‐immunoglobulin G involved heavy chain. Our study confirms that achievement of CR within 2 years from diagnosis is associated with improvement in survival outcomes and neutralization of the impact of FISH and ISS risk, thereby confirming observations from the clinical trial setting among a clinical practice cohort.